2008
DOI: 10.4049/jimmunol.180.5.3081
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes As a Short-Range Mechanism to Spread Alloantigen between Dendritic Cells during T Cell Allorecognition

Abstract: Exosomes are nanovesicles released by different cell types including dendritic cells (DCs). The fact that exosomes express surface MHC-peptide complexes suggests that they could function as Ag-presenting vesicles or as vehicles to spread allogeneic Ags for priming of anti-donor T cells during elicitation of graft rejection or induction/maintenance of transplant tolerance. We demonstrate that circulating exosomes transporting alloantigens are captured by splenic DCs of different lineages. Internalization of hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
224
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(228 citation statements)
references
References 51 publications
2
224
0
2
Order By: Relevance
“…Dendritic cells (DC) control T-cell-mediated immunity of EBV infection and control EBVdriven transformation (21,22). In addition, DC modulate adaptive immune responses by internalizing exosomes (23,24). To monitor whether exosomes transfer to primary immature monocyte-derived DC (MoDC), we labeled purified LCL exosomes with a green fluorescent lipid dye (PKH67) that could be made visible with confocal microscopy through capture by HLA-DR-coated beads ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dendritic cells (DC) control T-cell-mediated immunity of EBV infection and control EBVdriven transformation (21,22). In addition, DC modulate adaptive immune responses by internalizing exosomes (23,24). To monitor whether exosomes transfer to primary immature monocyte-derived DC (MoDC), we labeled purified LCL exosomes with a green fluorescent lipid dye (PKH67) that could be made visible with confocal microscopy through capture by HLA-DR-coated beads ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Once in the extracellular space, exosomes can bind to neighboring cells, bind locally, travel passively through the bloodstream for a more paracrine destination, or be taken up by marginal zone phagocytes in the spleen and liver [4,47].…”
Section: Fate Of Exosomesmentioning
confidence: 99%
“…2) (4, 26, 27), and this is likely to be the most fundamental pathway in vivo. Of particular note, it was shown that Dex priming of naive T cells can only occur if APCs are present (27)(28)(29). Two key mechanisms have been described for how antigenic peptide-MHC containing Dex could elicit indirect Ag presentation to T cells via an APC.…”
Section: The Composition Of Dex Determines Their Therapeutic Potentiamentioning
confidence: 99%